Discovery of a clandestine ticking bomb - blunt traumatic aortic injury - Abdul Rahim, Ezamin; Abdul Rashid, Aida; Mohamed, Ahmad Suhailan; Tan, Yee Ling; Mohd Sidek, Shahrin; Jamil, Hariati; Suppiah, Subapriya (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Blunt traumatic aortic injury (BTAI) is a crucial diagnosis to be made early in the management of trauma patients with aims to improve survival outcome. The objective of this case report is to highlight and explore the role of imaging especially Computed Tomography Angiography (CTA) thorax to diagnose a focal traumatic aortic isthmus pseudoaneurysm in a young gentleman sustaining high impact thoracic trauma.